Effective Diagnosis of Heart Disease through Bagging Approach - My Chau Tu; Dongil Shin; DongKyoo Shin (2009 2nd International Conference on Biomedical Engineering and Informatics, 2009)
The diagnosis of heart disease is important issue, prompting many researchers to work on development of intelligent medical decision support systems to improve the ability of physicians. In this paper, we propose the use of a bagging algorithm to indentify the warning signs of heart disease in patients and also to compare the effectiveness of the bagging algorithm with the decision tree algorithm that has been used by many researchers.